Developing a Novel Terahertz Fabry–Perot Microcavity Biosensor by Incorporating Porous Film for Yeast Sensing - Kim, Hwan Sik; Jun, Seung Won; Ahn, Yeong Hwan (Sensors, 2023)
We present a novel terahertz (THz) Fabry–Perot (FP) microcavity biosensor that uses a porous polytetrafluoroethylene (PTFE) supporting film to improve microorganism detection. The THz FP microcavity confines and enhances fields in the middle of the cavity, where the target microbial film is placed with the aid of a PTFE film having a dielectric constant close to unity in the THz range. The resonant frequency shift increased linearly with increasing amount of yeasts, without showing saturation behavior under our experimental conditions. These results agree well with finite-difference time-domain (FDTD) simulations. The sensor’s sensitivity was 11.7 GHz/μm, close to the optimal condition of 12.5 GHz/μm, when yeast was placed at the cavity’s center, but no frequency shift was observed when the yeast was coated on the mirror side. We derived an explicit relation for the frequency shift as a function of the index, amount, and location of the substances that is consistent with the electric field distribution across the cavity. We also produced THz transmission images of yeast-coated PTFE, mapping the frequency shift of the FP resonance and revealing the spatial distribution of yeast.
Keywords: Fabry-Perot cavity; Fabry-Perot microcavities; Frequency shift; Microbial films; Microorganisms detections; Polytetrafluoroethylene films; Porous film; Resonant frequency shift; Tera Hertz; Terahertz range; Electricity; Motion Pictures; Polytetrafluoroethylene; Porosity; Saccharomyces cerevisiae; Fabry–Perot cavity; microorganisms; porous film